Penerapan Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (Stad) dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran PAI di SMPN 4 Tarogong Kidul (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the effectiveness of the Student Team Achievement Division (STAD) cooperative learning model in improving student learning outcomes in Islamic Religious Education (PAI). The study used a quantitative approach with a one-group pretest-posttest experimental design. The research subjects consisted of 18 ninth-grade students of SMPN 4 Tarogong Kidul Garut. Data were collected through observation sheets of learning implementation and learning outcome tests given before and after the treatment. Data analysis was carried out using descriptive statistics, the Wilcoxon test, and the N-Gain test. The results showed that the implementation of the STAD model was well implemented based on observations of teacher and student activities during the learning process. Empirically, there was an increase in learning outcomes as indicated by an increase in the average student score from 50.28 in the pretest to 86.39 in the posttest. The results of the Wilcoxon test showed a significant difference between the pretest and posttest scores, which indicated that the implementation of the STAD model had a real effect on student learning outcomes. Furthermore, the N-Gain test results were in the moderate to high category, indicating that the improvement in students' abilities was not only statistically significant but also practically meaningful. Thus, the STAD cooperative learning model is effective in improving student learning outcomes in Islamic Religious Education (PAI), particularly the material on qada and qadar.